Penerapan Filsafat Realisme dalam Pendidikan: Analisis Dampaknya terhadap Metode Pembelajaran dan Dinamika Pendidikan Modern - mohammad yahya; Dyah Nawangsari; Hepni Zain; Ubaidillah Ubaidillah (EDUSHOPIA : Journal of Progressive Pedagogy, 2025)
The objective of this research is to analyze the application of realism philosophy in the context of education and its impact on teaching methods. Education based on realism emphasizes teaching rooted in reality and the objective world, where knowledge and skills are acquired through direct experience and observation of the surrounding environment. This study employs a literature review method, examining various references and literature related to realism philosophy and its implementation in education. Realism significantly contributes to the development of a factual knowledge-based curriculum; however, its application faces challenges, such as reliance on overly objective approaches and a lack of flexibility in accommodating individual student needs. While realism provides an effective approach to shaping students' character and knowledge, its implementation must adapt to the dynamics of modern education, which increasingly emphasizes creativity and practical skills development. Therefore, it is crucial to strike a balance between reality-based teaching and innovation in educational methods.